LEMBAR KERJA SISWA BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MEMFASILITASI KEMAMPUAN LITERASI MATEMATIS SISWA - Khairunnisak, Futri; Armis, Armis; Sakur, Sakur (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2025)
AbstractMathematical literacy is a crucial skill, yet many students still struggle with solving contextual problems due to limited supporting materials such as student worksheets (LKPD). This study is a research and development (R&D) study employing the 4D model (Define, Design, Develop, and Disseminate) aimed at producing a student worksheet based on Contextual Teaching and Learning (CTL) that is both valid and practical. The developed content focuses on systems of linear equations in two variables. The worksheet was validated by three mathematics education experts, tested through a one-to-one evaluation with three students, and a small group test with 22 eighth-grade students from a public junior high school in Riau Province. Validation results showed the worksheet to be highly valid in terms of content, construct, CTL approach, and mathematical literacy. The practicality test indicated that the worksheet was practical in terms of appearance, presentation, and usefulness. It can be concluded that the developed worksheet is both valid and practical. Further research is suggested to examine its effectiveness and adaptability to other topics or grade levels. AbstrakKemampuan literasi matematis penting dimiliki siswa, namun masih banyak yang mengalami kesulitan dalam menyelesaikan masalah kontekstual karena keterbatasan LKPD yang mendukung. Penelitian ini merupakan penelitian pengembangan (R&D) dengan model 4D (Define, Design, Develop, Disseminate) yang bertujuan menghasilkan LKPD berbasis Contextual Teaching and Learning (CTL). Materi yang dikembangkan berfokus pada sistem persamaan linear dua variabel. LKPD divalidasi oleh tiga dosen pendidikan matematika, diuji melalui one-to-one evaluation dengan tiga siswa, serta small group testdengan 22 siswa kelas VIII dari salah satu SMP Negeri di Provinsi Riau. Hasil validasi menunjukkan LKPD sangat valid dari segi isi, konstruksi, pendekatan CTL, dan literasi matematis. Uji kepraktisan menunjukkan LKPD tergolong praktis dari aspek tampilan, penyajian, dan manfaat. Dengan demikian, LKPD yang dikembangkan dinyatakan valid dan praktis. Penelitian selanjutnya disarankan untuk menguji efektivitas serta mengadaptasikan LKPD ini pada topik atau jenjang yang berbeda.